Applied of The Simulation of The Queue System in Restaurant Mie Gacoan Branch Gresk Using Arena 14.0 - Ristanti, Dwi Mei; Prawira, Firdaus; Sumariyono, Eko (UNIPA PRESS, 2024)
A system design certainly cannot be separated from the term simulation. There is no need to calculate the simulation manually because a system called the Arena application is available. The Arena is a windows-based simulation software used to simulate and analyze a system. This study aims to enable the practitioner to know and run a queuing system simulation into the tools in the Arena 14.0 software, which in turn can apply it in real conditions to the queuing system at Mie Gacoan Restaurant Gresik Branch. The method used in this case is the simulation queuing method. The queuing model consists of 2 single servers consisting of a general queue and an online ojek queue. The simulation queuing presentation uses the FIFO (first in, first out) rule. That is, consumers who come first to make payments are the first to be served by the system. The analysis results show that the queue rate on server 2 (online ojek queue) has a slightly longer time difference than on server 1 (general queue).